Pengaruh Perubahan Iklim pada Musim Tanam dan Produktivitas Jagung (Zea mays L.) di Kabupaten Malang - Ninuk Herlina; Amelia Prasetyorini (Institut Pertanian Bogor, 2020)
Maize (Zea mays L.) is one of the agricultural commodities used as food and has quite a lot of benefits. The highest Indonesian production data is found in East Java. Malang Regency is one of the highest maize-producing areas in East Java. However, the production and productivity of maize in Malang Regency has fluctuated. One of the causes of unstable maize production in Indonesia is climate change due to global warming. Climate change that affect the length of the rainy and dry season is change in rainfall patterns. The purpose of this research is evaluating whether climate change occurred in 1998-2017 in Malang Regency and to know the impact of climate change on the growing season and corn productivity in Malang Regency. The study was conducted from February to May 2018 in Donomulyo, Dau, and Kasembon sub-district, Malang Regency. The research was carried out by survey method using primary and secondary data. The results showed that the climate in the North Malang Regency had undergone a change, which was marked by the increase in rainfall and monthly temperature and changes in climate type, while in the South it was marked by the decrease in monthly rainfall, monthly rainy days, and temperatures. The elements of rainfall and rainy days do not affect maize productivity, while the temperature has a corelation and has a significant effect on the maize productivity. Temperature has a positive effect on maize productivity and a model of estimating the effect of temperature on productivity was obtained, namely Y = -38552+1836 X. The impact of climate change is the occurrence of a shift in the beginning of the rainy and the dry seasons which cause changes in the maize planting season. Keywords: climate change, planting season, productivity of maize